Long-term follow-up study on obstructive hypertrophic cardiomyopathy patients treated with disopyramide: evidences of a notable trend in symptom control within a real-world clinical setting - Todde, Gaetano; Dei, Lorenzo Lupo; Polizzi, Roberto; Gabrielli, Domenico; Canciello, Grazia; Romano, Silvio; Borrelli, Felice; Halasz, Geza; Ordine, Leopoldo; Di Napoli, Salvatore; Pacella, Daniela; Lombardi, Raffaella; et al. (Frontiers in Cardiovascular Medicine, 2024)
In obstructive hypertrophic cardiomyopathy (HOCM), disopyramide is used in patients who remain symptomatic despite β-blockers or verapamil. However, effectiveness of disopyramide therapy has not been clearly established due to inconsistent definition of responders and the insufficient length of follow-ups reported in literature. To address these shortcomings, we have conducted a retrospective analysis from detailed databases with long follow-up, from two HCM Referral Centers.. 62 symptomatic HOCM patients (43% women, age 52±14 years) with left ventricular (LV) outflow tract gradient (LVOTG) ≥50 mmHg at rest or during provocation, were recruited from two Italian Centers. Disopyramide was added as second-line therapy in the patients in whom symptoms persisted despite classic pharmacologic treatment. Patients in NYHA class >II at baseline who reached NYHA class II or I, and patients in NYHA class II at baseline who reached NYHA class I or symptoms stabilization were defined as responders.Results. At follow-up, (mean 4.4 years, IQR 1.1-6.6 years), 47 patients (76%) were responders, whereas 15 (24%) were no-responders. Responders showed larger LV diastolic volume index (LVEDVi) at baseline as compared to no-responders (61±14vs 49±16 ml, respectively, p=0.018), and, at follow-up, reached lower LVOTG than no-responders (43 ±32 vs 66 ±28 mmHg, respectively, p=0.013), with a LVOTG <50 mmHg more represented in responders than in noresponders (75% vs 25%, respectively; p=0.004). No side effects requiring discontinuation of the therapy were recorded.HOCM patients treated with disopyramide as second-line therapy in a quite longfollow-up showed a significant improvement of symptoms, which avoided SRT in up to 70% of them. Moreover, our data suggest that a larger LVEDVi at baseline identify the subgroup of patients who benefit the most from the therapy in terms of symptoms and reduction of LVOTG below 50 mmHg during treatment. We will discuss specific situations where disopyramide may be preferred over myosin inhibition to ensure that effective therapeutic options are fully considered and not prematurely dismissed.